The Effect of Cyclophosphamide Chemotherapy on Ovarian AntiMÃ¼llerian Hormone Levels in Breast Cancer Patients - Elisabeth G.K. Liga; Nusratuddin Abdullah; Eddy Tiro; St. Maisuri T. Chalid (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To evaluate cyclophosphamide effects on Anti-MÃ¼llerian hormone (AMH) levels in breast cancer patientstreated with cyclophosphamide chemotherapy.Methods: This cohort prospective study was conducted inDr. Wahidin Sudirohusodo Hospital in the Department of Obstetricsand Gynecology in collaboration with Department of Surgery,Faculty of Medicice, Universitas Hasanuddin between September2015 and June 2016. Serum levels of AMH from forty breast cancerpatients received three series of cyclophosphamide chemotherapydetermined by Enzyme Linked Immuno Sorbent Assay (ELISA).Results: Serum AMH levels decreased significant in the first series(from 2.09ï‚±2.04 ïg/ml to o.65ï‚±1.06 ïg/ml; p<0.05) through thethird series (from 1.53ï‚±1.34 ïg/ml to 0.5ï‚±0.65 ïg/ml; p<0.05) ofcyclophosphamide chemotherapy.Conclusion: AMH levels decreased significant after cyclophosphamideindicated that cyclosphosphamide decrease ovarianreserve.[Indones J Obstet Gynecol 2018; 6-1: 64-67]Keywords: anti-mÃ¼llerian hormone, breast cancer, cyclophosphamide,ovarian reserveObjective: To evaluate cyclophosphamide effects on Anti-MÃ¼llerian hormone (AMH) levels in breast cancer patientstreated with cyclophosphamide chemotherapy.Methods: This cohort prospective study was conducted inDr. Wahidin Sudirohusodo Hospital in the Department of Obstetricsand Gynecology in collaboration with Department of Surgery,Faculty of Medicice, Universitas Hasanuddin between September2015 and June 2016. Serum levels of AMH from forty breast cancerpatients received three series of cyclophosphamide chemotherapydetermined by Enzyme Linked Immuno Sorbent Assay (ELISA).Results: Serum AMH levels decreased significant in the first series(from 2.09ï‚±2.04 ïg/ml to o.65ï‚±1.06 ïg/ml; p<0.05) through thethird series (from 1.53ï‚±1.34 ïg/ml to 0.5ï‚±0.65 ïg/ml; p<0.05) ofcyclophosphamide chemotherapy.Conclusion: AMH levels decreased significant after cyclophosphamideindicated that cyclosphosphamide decrease ovarianreserve.Keywords: anti-mÃ¼llerian hormone, breast cancer, cyclophosphamide,ovarian reserve